Eksistensi Pendidikan Karakter Islami Berbasis Kearifan Lokal dan Relevansinya Terhadap Program Merdeka Belajar Kampus Merdeka - Haidir Haidir; Muhammad Hizbullah; M. Guffar Harahap; Ardat Ardat; Azrai Harahap (Fitrah: Journal of Islamic Education, 2023)
Islamic character education is the most important and urgent thing to be applied at various levels of education, both in primary, secondary and tertiary education, one of which is through local wisdom. With regard to that, this research aims to analyze the existence of Islamic character education based on local wisdom at UMN Al-Washliyah Medan. This research uses a qualitative description analysis method, by first collecting facts and data accurately and then tabulating them so that conclusions will be obtained. Data collection uses observation, interviews and documentation studies. The results of the study explain that, namely 1) UMN Al-Washliyah Medan is one of the PTU campuses that implements Islamic character education directly through lecture activities and outside lectures with the habituation method. 2) The existence of character education implemented at UMN Al-Washliyah Medan towards the era of independent learning is carried out with several models, namely habituation activities, exemplary, discipline, with rewards and punishments, with active / contextual and participatory learning. The local wisdom can be seen from the existence of Al-Washliyahan courses, one of which fosters student character.